# Linear Equations

Views:

Category: Entertainment

## Presentation Description

No description available.

## Presentation Transcript

### Linear Equations in two VARIABLES:

Linear Equations in two VARIABLES

### Review video from last week’s lecture:

Review video from last week’s lecture

### System of equations:

System of equations A pair of linear equations in two variables is said to form a system of simultaneous linear equations. For example: 2x – 3y +4 = 0 and x + 7y -1 = 0 These two equations form a system of two linear equations in variables x and y.

### Continue…:

Continue… The general form of a linear equation x and y is Ax + by +c = 0, where a and b is not equal to zero and are real numbers. A solution of such an equation is a pair of values. One is for x and the other for y. Once the values of x and y are represented the two sides of the equation hold for them to be equal. Every linear equation in two variables has infinitely many solutions which can be represented on a certain line.

### Graphical Solutions of a Linear Equation:

Graphical Solutions of a Linear Equation Let us consider the following system of two simultaneous linear equations in two variable: 2x-y=-1 and 3x+2y=9 Here we assign any value to one of the two variables and then determine the value of the other variable from the given solution by using a t-chart

### T-chart:

T-chart For the equation: 2x-y=-1 solve for y y=2x+1 Plug x=0,2 to get y values 3x+2y=9 solve for y y=9-3x Plug x=3,-1 to get y values Any questions on how to Complete t-chart? x 0 2 y 1 5 x 3 -1 y 0 6

### Graph equations:

Graph equations X Y 0 1 2 5 X Y 3 0 -1 6 Y=2x+1 Y=9-3x

### Algebraic methods of solving liner equations:

Algebraic methods of solving liner equations The most common used algebraic methods of solving simultaneous linear equations in two variables are: Method of by substitution. Method by equating the coefficient. Method by elimination

### Method by Substitution:

Method by Substitution Solve the equations given by solving for x and substitute the x-value of ( i ) first equation into (ii) second equation to get one equation ( i ) x+2y=-1 and (ii)2x-3y=12 ( i ): x=-2y-1 plug this equation into (ii) by substituting value of x 2(-2y-1)-3y=12 distribute and simplify -4y-2-3y=12 combine like terms and solve for y -7y-2=12 -7y=14 y=-2 putting the value of y in equation ( i ) w get x =-2y-1 x=-2(-2)-1 x=3 Hence solution of the equation is (3,-2)

### Use Method by Substitution :

Use Method by Substitution Try on your own Use previous slide to solve for x and y in these two equations given: y=5x-1 and 2y=3x+12

### Solution:

Solution y=5x-1 ( i ) and 2y=3x+12 (ii) Step 1: substitute ( i ) into (ii) from y value. Step 2: 2(5x-1)=3x+12 distribute Step 3: 10x-2=3x+12 combine like terms to solve for x Step 4: 7x-2=12 7x=14 x=2 Step 5: Use value of x to solve for y in ( i ) equation Step 6: y=5(2)-1 y=9 Step 7: Solution: x=2 and y=9, check your work by plugging in these values in both equations to make sure left equals right in both equations. Any questions?

### Method by Elimination:

Method by Elimination In this method, we eliminate one of the two variable which can easily be solved. Putting the value of this variable in any of the given equations. The value of the other variable can be obtained. For example we want to solve: 3x+2y=11 and 2x+3y=4

### Continue…:

Continue… ( i ) 3x+2y=11 and (ii) 2x+3y=4 First we can use a method by equating the coefficient which means multiplying ( i ) by 3 and (ii) by -2. We get 3(3x+2y=11)------9x+6y=33 -2(2x+3y=4)------- -4x-6y=-8 Now we can eliminate y values by adding both ( i ) and (ii) 9x+6y=33 + -4x-6y=-8 ---------------- 5x=25 solve for x x=5

### Continue…:

Continue… Putting the value of y in equation ( i ) 3x+2y=11 3(5)+2y=11 15+2y=11 2y=-4 y=-2 Solution: x=5 and y=-2 Check solutions

### Use Method by Elimination:

Use Method by Elimination Try on your own Use previous slides to solve for x and y in these two equations given: x+3y=-5 and 4x-y=6

### Solution:

Solution x+3y=-5 ( i ) and 4x-y=6 (ii) Step 1: Multiply ( i ) by -4 to eliminate x. Step 2: -4(x+3y=-5)------- -4x-12y=20 Step 3: Add both equations and combine like terms to eliminate x. Step 4: 4x-y=6 + -4x-12y=20 ---------------------- -13y=26 -y=2…..multiply by (-1)….. y=-2 Step 5: Plug in y=-2 into equation ( i ) x+3(-2)=-5…. x-6=-5 x=1 Step 6: Check solutions

### Review:

Review Given two equations, with two variables, we are then able to use different methods to solve for x and y Once we found the values of x and y, are we finished? We need to make sure both values hold for both equations. What are the two methods we went over? The methods are methods by substitution and method by elimination. Any questions?